Notes on rapid resource assessments in Tanabag River and Coastal Area of Sta. Lucia, Puerto Princesa City, Palawan, Philippines - Jose, Edgar D. (2015)
This report presents the results of a rapid biodiversity assessment of a freshwater and brackish water ecosystem in the City of Puerto Princesa.
Keywords: Freshwater ecosystem; Brackishwater ecosystem